Comparison of different methodologies for DNA extraction from Aegla longirostri - Bitencourt,João Vitor Trindade (2007)
The aim of this study was to compare some DNA extraction methodologies for Aegla longirostri. The protocols were based on the traditional phenol-chloroform DNA extraction methodology and using a commercial kit for DNA extraction. They differed in tissues used, the addition - or not - of beta-mercaptoethanol to the lysis buffer, times and methods for the animal's conservation (frozen, in ethanol or fresh). Individuals stored at -20°C for a long time supplied lower molecular weight DNA than those stored for a short time. The best yield for the specimens preserved in ethanol was obtained for 15 days storage in 95% ethanol. The kit resulted in a low quantity of high molecular weight DNA. The best protocol for DNA extraction from Aeglidae, and probably for other crustaceans should, therefore, utilize fresh specimens, with addition of beta-mercaptoethanol to the lysis buffer.